2010
DOI: 10.5352/jls.2010.20.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Inhibitory Effect on Streptococcus mutans by Oleanolic Acid

Abstract: Among endogenous oral microflora, Streptococcus mutans plays a critical role in dental plaque formation, which mainly contributes to the development of caries and periodontal disease. Phytochemicals are plant-derived chemical compounds that have been studied as beneficial nutrients to human health. The purpose of this study was to determine the effects of phytochemicals against S. mutans. Among them, oleanolic acid (OA) and 5-(hydroxymethyl)-2-furfural (HF) from Thomson seedless raisins were tested for anti-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…faecium , Streptococcus mutans , and Streptococcus sanguis [ 1 , 2 , 3 , 4 ]. There was weaker antimicrobial effect against Gram-negative bacteria, however, including Acinetobacter baumannii , Burkholderia thailandensis , Escherichia coli , Klebsiella pneumoniae , and Pseudomonas aeruginosa [ 9 ]. This difference can be explained by the presence of the outer membrane of Gram-negative bacteria, which possesses multiple drug efflux pumps [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…faecium , Streptococcus mutans , and Streptococcus sanguis [ 1 , 2 , 3 , 4 ]. There was weaker antimicrobial effect against Gram-negative bacteria, however, including Acinetobacter baumannii , Burkholderia thailandensis , Escherichia coli , Klebsiella pneumoniae , and Pseudomonas aeruginosa [ 9 ]. This difference can be explained by the presence of the outer membrane of Gram-negative bacteria, which possesses multiple drug efflux pumps [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies demonstrated that oleanolic acid inhibits the growth of Listeria monocytogenes , suggesting the potential usefulness of the compound as a food additive with anti-listerial activity [ 8 ]. In addition, it was shown that oleanolic acid inhibited the growth of Gram-positive bacteria, but this inhibition effect was weaker in Gram-negative bacteria [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are negative perceptions regarding synthetic additives, and natural materials are attractive as alternative antimicrobial agents because of their limited effects on the environment and their low toxicity to human cells( Kaya et al , 2008 ). Various lifeforms, including microorganisms, plants, and animals, have been investigated to identify novel antimicrobial agents that possess these favored characteristics ( Guliani et al , 2007 ; Yoon and Choi, 2010 ).…”
Section: Introductionmentioning
confidence: 99%